Relative age effect on student-athletes of Mato Grosso state (Brazil) participating in the National School Games depending on sex, age category, and sport type - DE OLIVEIRA CASTRO, Henrique; DA SILVA, Willian José Bordin; Dos Santos Nascimento, Carla Danielly; DE CASTRO RIBEIRO, Lucas; DA SILVA AGUIAR, Samuel; Aburachid, Layla Maria Campos; DE OLIVEIRA, Vivian [UNESP]; Figueiredo, Lucas Savassi (Termedia Sp. z.o.o., 2023)
Purpose. The relative age effect (RAE) is a widely reported phenomenon in elite sports context. However, little is known about its occurrence in other levels of practice, such as school sports. Thus, this study aimed to investigate the presence of RAE on Mato Grosso state (Brazil) student-athletes participating in National School Games depending on sex, age category, and sport type. Methods. Data from 440 student-athletes of Mato Grosso state (Brazil) who participated in 2 National School Games: 2019 Youth School Games (n = 250) and 2021 Brazilian School Games (n = 190) were organized depending on their quarters of birth. Chi-square tests were performed to compare their birthdates distribution in accordance with sex (male and female), age category (12–14 years old and 15–17 years old), and sport type (team and individual sports). Results. Athletes born in the first months of the year were more frequent than athletes born in the last months of the year in the overall sample, in males, in the younger age category, and in team sports (p < 0.008). On the other hand, no differences were found for females, athletes from the older age category, or athletes practising individual sports (p > 0.05). Conclusions. RAE is pervasive in the student-athletes of Mato Grosso state (Brazil), specifically for male athletes in early categories of team sports. Educating coaches regarding this effect and implementing specific counter-RAE interventions are warranted to minimize selection bias in this sports context.
Keywords: aptitude; selection bias; youth sports